Conditional deletion of ELL2 induces murine prostate intraepithelial neoplasia. Issue 2 (November 2017) - Pascal, Laura E; Masoodi, Khalid Z; Liu, June; Qiu, Xiaonan; Song, Qiong; Wang, Yujuan; Zang, Yachen; Yang, Tiejun; Wang, Yao; Rigatti, Lora H; Chandran, Uma; Colli, Leandro M; et al.
Abstract : Elongation factor, RNA polymerase II, 2 (ELL2) is an RNA Pol II elongation factor with functional properties similar to ELL that can interact with the prostate tumor suppressor EAF2. In the prostate, ELL2 is an androgen response gene that is upregulated in benign prostatic hyperplasia (BPH). We recently showed that ELL2 loss could enhance prostate cancer cell proliferation and migration, and that ELL2 gene expression was downregulated in high Gleason score prostate cancer specimens. Here, prostate-specific deletion of ELL2 in a mouse model revealed a potential role for ELL2 as a prostate tumor suppressor in vivo . Ell2 -knockout mice exhibited prostatic defects including increased epithelial proliferation, vascularity and PIN lesions similar to the previously determined prostate phenotype in Eaf2 -knockout mice. Microarray analysis of prostates from Ell2 -knockout and wild-type mice on a C57BL/6J background at age 3 months and qPCR validation at 17 months of age revealed a number of differentially expressed genes associated with proliferation, cellular motility and epithelial and neural differentiation. OncoPrint analysis identified combined downregulation or deletion in prostate adenocarcinoma cases from the Cancer Genome Atlas (TCGA) data portal. These results suggest that ELL2 and its pathway genes likely play an important role in the development and progression of prostate cancer.